1998
DOI: 10.1002/(sici)1096-8628(19980907)81:5<364::aid-ajmg4>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

A genome-wide search for schizophrenia susceptibility genes

Abstract: We completed a systematic genome-wide search for evidence of loci linked to schizophrenia using a collection of 70 pedigrees containing multiple affected individuals according to three phenotype classifications: schizophrenia only (48 pedigrees; 70 sib-pairs); schizophrenia plus schizoaffective disorder (70 pedigrees; 101 sib-pairs); and a broad category consisting of schizophrenia, schizoaffective disorder, paranoid or schizotypal personality disorder, psychosis not otherwise specified (NOS), delusional disor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
131
1
2

Year Published

1999
1999
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 236 publications
(145 citation statements)
references
References 52 publications
11
131
1
2
Order By: Relevance
“…[16][17][18] There is also suggestive evidence for linkage of both schizophrenia and bipolar disorder to chromosome 22q (reviewed in Karayiourgou and Gogos 19 ; see also [20][21][22][23] ). Early studies on biochemical markers for schizophrenia reported higher COMT activity in patients compared to controls (reviewed in Baron et al 24 ), but these results were not conclusive.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18] There is also suggestive evidence for linkage of both schizophrenia and bipolar disorder to chromosome 22q (reviewed in Karayiourgou and Gogos 19 ; see also [20][21][22][23] ). Early studies on biochemical markers for schizophrenia reported higher COMT activity in patients compared to controls (reviewed in Baron et al 24 ), but these results were not conclusive.…”
Section: Introductionmentioning
confidence: 99%
“…Lindholm et al 14 reported, in one very large SZ pedigree of Sweden, a lod score of 6.6 in 6q25.2 and described a 6 cM haplotype in this region segregating with the disorder. However, we 15 and others, [16][17][18][19][20][21][22] as well as a meta-analysis, 23 reported negative results in 1q21-q22, whereas two studies 24,25 provided confirmations.…”
mentioning
confidence: 52%
“…7,[12][13][14][15][16][17][18][19][20][21][22] Fine mapping and haplotype analysis of the linkage peak in an Icelandic sample identified a haplotype, shared by seven out of the thirty-three families tested, implicating an B600 kb region. 7 A core haplotype from this region (Hap ICE ) spanning 290 kb and consisting of five singlenucleotide polymorphisms (SNPs) and two microsatellite markers was found to be over-represented in affected individuals (P = 0.000087, one-tailed; Figure 1).…”
Section: Introductionmentioning
confidence: 99%